Empirical evidence on examining the performance of accounting major / Nor Syafinaz Shaffee, Dr Normah Ahmad and Fazni Mohd Fadzillah - Ahmad, Normah; Mohd Fadzillah, Fazni (Research Management Institute (RMI), 2011)
Students' performance in Costing 1 (MAF220) had been fluctuating. The failure rate frequently exceed the required standard of the Faculty of Accountancy where the failure rate should be less than 20%. Thus, a study was carried out to explore the characteristics of students taking up Costing 1 (MAF220) at UiTM (Perlis). Questionnaires were distributed to final year students of April 2010. Attributes set in the questionnaire were based on the previous researches whom had associated personal attribute, intention, prior exposure, disruption and gender differences for the cause of variation in students' performance. This study has found that students' performances and attrbutes influence their intention to further their study in cost-related studies (CIMA). Further study should look into how significant the attributes could influence the performance of students in MAF220 and thus, could teachercentred or student-centred learning be implemented.